Effect of Proton Pump Inhibitor Use on the Gut Microbiome and Risk of Clostridium difficile Infection in Hospitalized Patients: A systematic review and Meta-Analysis - Michael Thomas Ebner, Sebastian Fabian Pichler, Florian Manuel Auer (Academic Journal of Clinicians, 2024)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder characterized by ovulatory dysfunction. Both letrozole and clomiphene citrate have been used as first-line pharmacological agents for ovulation induction in PCOS, but their relative efficacy requires further investigation. Objective: To compare the efficacy of letrozole versus clomiphene citrate for ovulation induction in women with PCOS. Methods: This was a randomized, double-blind, controlled trial conducted at a tertiary care center. Infertile women with PCOS were randomly assigned to receive either letrozole or clomiphene citrate for up to 6 ovulatory cycles. The primary outcome was the ovulation rate per cycle. Secondary outcomes included pregnancy rate, time to ovulation, and adverse effects. Results: A total of 320 women with PCOS were included in the analysis, with 160 in the letrozole group and 160 in the clomiphene citrate group. The ovulation rate per cycle was significantly higher in the letrozole group compared to the clomiphene citrate group (79.4% vs. 65.9%, p<0.001). The pregnancy rate was also higher in the letrozole group (27.5% vs. 19.4%, p=0.048). The time to ovulation was shorter in the letrozole group (12.6 ± 3.2 days vs. 15.1 ± 4.1 days, p<0.001). The incidence of adverse effects was similar between the two groups. Conclusions: Letrozole is more effective than clomiphene citrate for ovulation induction in women with PCOS, with higher ovulation and pregnancy rates, as well as a shorter time to ovulation. These findings support the use of letrozole as a first-line pharmacological agent for the management of ovulatory dysfunction in PCOS.